Lactate levels in severe malarial anaemia are associated with haemozoin-containing neutrophils and low levels of IL-12. - Casals-Pascual, C; Kai, O; Lowe, B; English, M; Williams, T; Maitland, K; Newton, C; Peshu, N; Roberts, D (2006)
BACKGROUND: Hyperlactataemia is often associated with a poor outcome in severe malaria in African children. To unravel the complex pathophysiology of this condition the relationship between plasma lactate levels, parasite density, pro- and anti-inflammatory cytokines, and haemozoin-containing leucocytes was studied in children with severe falciparum malarial anaemia. METHODS: Twenty-six children with a primary diagnosis of severe malarial anaemia with any asexual Plasmodium falciparum parasite density and Hb < 5 g/dL were studied and the association of plasma lactate levels and haemozoin-containing leucocytes, parasite density, pro- and anti-inflammatory cytokines was measured. The same associations were measured in non-severe malaria controls (N = 60). RESULTS: Parasite density was associated with lactate levels on admission (r = 0.56, P < 0.005). Moreover, haemozoin-containing neutrophils and IL-12 were strongly associated with plasma lactate levels, independently of parasite density (r = 0.60, P = 0.003 and r = -0.46, P = 0.02, respectively). These associations were not found in controls with uncomplicated malarial anaemia. CONCLUSION: These data suggest that blood stage parasites, haemozoin and low levels of IL-12 may be associated with the development of hyperlactataemia in severe malarial anaemia.